A Juridical Analysis of Inpatient Care Implementation Based on BPJS Hospital Class Standards - R.Pratama; S.Wijaya (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: The transformation of Indonesian healthcare relies heavily on the implementation of the Social Security Administrator for Health (BPJS Kesehatan). A pivotal shift occurs with the transition from the traditional multi-tiered treatment classes to the unified Standard Inpatient Class (KRIS) system. This study evaluates the legal framework and readiness of healthcare facilities to implement these new standards. Methods: This research utilizes a juridical-normative approach, analyzing primary, secondary, and tertiary legal sources. Statutory analysis and conceptual approaches are applied to assess the alignment of health regulations with operational realities. Results: The findings reveal a significant legal and infrastructural gap between the mandated KRIS parameters and the actual capacities of regional hospitals. While the regulations aim to democratize healthcare quality, the rigid requirements strain local resources and compromise immediate service delivery. Discussion: The transition exposes critical friction within health law principles, particularly balancing standardized equity with the realities of decentralized hospital funding. Literature indicates that mandatory uniformity without proportional fiscal support risks reducing total available bed capacity, thereby exacerbating patient wait times. Legally, the enforcement mechanism lacks sufficient transition protections for lower-tier hospitals. Conclusions: Successful implementation of the BPJS standard inpatient class requires synchronized regulatory updates and targeted state subsidies to prevent infrastructure deficits. Immediate revisions to the enforcement timeline are essential to safeguard universal health coverage principles.